Behavioural Finance a Study on Investors Behaviour towards Equity Market Investment with Reference to Investors of Delhi: Understanding the Behavior and Decision-Making of Investors in the Equity Market (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Contributing judiciously is an important part of financial security. An Individual is always looking for such an investment alternatives which give maximum and faster returns. As it is verifiable truth that more returns is being accompanied by more hazard. The one such alternative of these sort for example faster comes back with more hazard is the investment in stock market. It is being seen over some undefined time frame that the individuals are attracting towards stock market because of the liquidity and multifold returns, although the proportion of loss of assets contributed by the investors is also high at certain instances. Therefore the present study is a small attempt to understand the basic brain research of an Investor towards stock market and different parameters and factors related to it. The study is based on a rational to understand the basic facts and belief systems an investor is carrying about the stock market in general and in explicit Investment preference mainly centers upon how investor examines and acts on information to take investment decisions. The study attempts to elucidate the very factor that is Subjective brain research the study of how individuals (counting investors) think, reason, and make decisions. It reveals that individuals don't always act insightfully with regards to making financial decisions and that their behaviors impacts them in making investment decisions. The sample size of the study is 61 representatives of construction companies in Mysuru city. The sampling system utilized was basic random sampling. Primary data was been utilized in the study, which was gathered through organized questionnaire which is prepared based on behavioral finance and investment preference. Various statistical tools was utilized for analyzing the data like Engaging Statistics, t-Test Statistical Tool, Correlation Tool and Percentage Analysis. The study attempted to understand the irrational decisions taken by the investors during the hour of putting resources into a particular avenue. Through the study, it is recognized that construction representatives of Mysuru city are aware about the various potential outcomes in investments and it is discovered that there exist a relationship between behavioral finance and investment preference among representatives of construction companies.